Optimization of callus induction and proliferation of Paeonia lactiflora Pall. and Agrobacterium-mediated genetic transformation - Duan, Siyang; Xin, Rujie; Guan, Shixin; Li, Xueting; Fei, Riwen; Cheng, Wan; Pan, Qing; Sun, Xiaomei (Frontiers in Plant Science, 2022)
Paeonia lactiflora Pall. is an important ornamental plant with high economic and medicinal value, which has considerable development prospects worldwide. The lack of efficient tissue culture techniques and genetic transformation systems has become a master obstacle for P. lactiflora research. The purpose of the present study focuses on obtaining an efficient and stable genetic transformation method using callus as the receptor and exploring an efficient protocol for callus induction and proliferation associated with P. lactiflora. Callus induction and proliferation were performed using MS medium with various concentrations of 2,4-Dichlorophenoxyacetic acid (2,4-D), 1-Naphthaleneacetic acid (NAA), 6-Benzylaminopurine (6-BA) and thidiazuron (TDZ). The sensitivity of callus to kanamycin and cefotaxime was determined. Several parameters such as Agrobacterium cell density, infection time and co-culture duration were studied to optimize transformation efficiency. Agrobacterium strains EHA105 and pBI121 binary vector harboring the β-glucuronidase (GUS) gene were used for transformation. Expression of the GUS reporter gene was detected by GUS assay, polymerase chain reaction (PCR) and Quantitative Real-time PCR (RT-qPCR). The MS medium containing 1.0 mg·L-1 NAA, 0.5 mg·L-1 2,4-D and 0.5 mg·L-1 TDZ was optimal for callus induction and MS medium containing 0.5 mg·L-1 NAA, 1.0 mg·L-1 2,4-D and 0.5 mg·L-1 TDZ was the best for callus proliferation. The concentrations of kanamycin and cefotaxime used for screening positive callus were 125 mg·L-1 and 200 mg·L-1, respectively. Among various combinations analyzed, the best transformation result was obtained via the 25 min of infection of Agrobacterium at 0.6 OD600 and 3 d of co-culture. Overall, this study provided technical support and theoretical guidance for improving the callus induction and proliferation efficiency and the study of gene function in P. lactiflora.